Diagnostic and Therapeutic Maneuvers for Anterior Canal BPPV Canalithiasis: Three-Dimensional Simulations - Bhandari, Anita; Bhandari, Rajneesh; Kingma, Herman; Strupp, Michael (Frontiers in Neurology, 2021)
Background and Objectives Anterior canal BPPV is a rare BPPV variant. Various diagnostic and therapeutic maneuvers have been described for its management. The aim of this study was to use three-dimensional simulation models to visualise otoconial debris movement within the anterior canal during diagnostic tests and different liberatory maneuvers. This can help to optimise existing treatment maneuvers and help in the development of better management protocols. Methods Based on reconstructed MRI images and fluid dynamics, a 3D dynamic simulation model (as a function of time) was developed and applied. Simulations of the supine head-hanging test for diagnosis of ac-BPPV were studied. Three repositioning maneuvers were simulated: (1) the Yacovino maneuver and its modifications, (2) the reverse Epley maneuver and (3) the short canal repositioning (CRP) maneuver. Results The simulation showed that the supine head-hanging test is a good test for diagnosis of ac-BPPV affecting both labyrinths and demonstrated why there is no inversion of nystagmus on sitting up. The Yacovino maneuver was seen to be an effective treatment option for ac-BPPV without having to determine the side involved. However, simulations showed that the classical Yacovino maneuver carried a risk of canal switch to the posterior canal. To overcome this risk, a modified Yacovino maneuver is suggested. The reverse Epley maneuver was not an effective treatment. Short CRP is useful in ac-BPPV treatment; however, it requires determination of side of involvement. Conclusions The 3D simulator of the movement of the otoconial debris presented here can be used to test the mechanism of action and the theoretical efficacy of existing diagnostic tests and maneuvers as well as to develop new treatment maneuvers to optimize BPPV treatment.